2016
DOI: 10.1186/s12906-016-1348-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of cytotoxicity between extracts of Clinacanthus nutans (Burm. f.) Lindau leaves from different locations and the induction of apoptosis by the crude methanol leaf extract in D24 human melanoma cells

Abstract: BackgroundClinacanthus nutans (Burm. f.) Lindau leaves are widely used by cancer patients and the leaf extracts possess cytotoxic and antiproliferative effects on several human cancer cell lines. However, the effect of C. nutans leaf extract on human melanoma, which is the least common but most fatal form of skin cancer and one of the most common cancers diagnosed in both sexes worldwide, is unknown. There is also limited information on whether the bioactivity of extracts differs between C. nutans leaves grown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…Ethanol extract of C. nutans has been shown to impede hepatoma in mice through induction of apoptosis and enhancement of immune response [ 9 ]. Researchers have also demonstrated that C. nutans methanol extract induces human melanoma cell apoptosis [ 10 ]. Despite claims regarding the use of C. nutans in treating various cancers, the anti-angiogenic potential of C. nutans has never been carefully examined.…”
Section: Introductionmentioning
confidence: 99%
“…Ethanol extract of C. nutans has been shown to impede hepatoma in mice through induction of apoptosis and enhancement of immune response [ 9 ]. Researchers have also demonstrated that C. nutans methanol extract induces human melanoma cell apoptosis [ 10 ]. Despite claims regarding the use of C. nutans in treating various cancers, the anti-angiogenic potential of C. nutans has never been carefully examined.…”
Section: Introductionmentioning
confidence: 99%
“…As example, Ng et al (2017) demonstrated that C. nutans hexane extract (150 μg/mL) induced apoptosis in CNE1 and HepG2 cells. Meanwhile, Fong et al (2016) reported that late apoptosis occurred in D24 melanoma cells treated with 2 mg/mL methanol (Figure 3(C)), the percentage of early apoptosis was 60.20 ± 2.17% after only 24 h of treatment. However, at 72 h treatment period, the number of early apoptotic cells were decreased to 4.53 ± 0.83%.…”
Section: Induction Of Apoptotic Cell Death Of Sf1mentioning
confidence: 95%
“…Highest cytotoxic activities were found in extract from Chiang Dao and Chiang Mai, Thailand, with the half maximal effective concentration (E50) of 0.95 mg/mL for 24 hours and E50 of 0.77 mg/mL for 72 hours. Chiang Dao extract also induced apoptosis in biochemical and morphological analyses of D24 cells [ 38 ]. These data suggest that C. nutans extracts and extracts of plants in higher elevations and lower temperature could be more promising for the treatment of skin cancer.…”
Section: Effects and Action Mechanism Studies Of C Nutans Extracts On Cancersmentioning
confidence: 99%